2008
DOI: 10.1021/es801070p
|View full text |Cite
|
Sign up to set email alerts
|

Alternate and New Brominated Flame Retardants Detected in U.S. House Dust

Abstract: Due to the voluntary withdrawals and/or bans on the use of two polybrominated diphenyl ether (PBDE) commercial mixtures, an increasing number of alternate flame retardant chemicals are being introduced in commercial applications. To determine if these alternate BFRs are present in indoor environments, we analyzed dust samples collected from 19 homes in the greater Boston, MA area during 2006. Using pure and commercial standards we quantified the following brominated flame retardant chemicals using GC/ECNI-MS m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
434
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(463 citation statements)
references
References 31 publications
18
434
11
Order By: Relevance
“…46,47 The relative abundances of TBB and TBPH were also quite small (<1%), probably because the commercial product Firemaster 550 containing these chemicals was only introduced in 2003. 48 A positive correlation (r 2 = 0.53; p < 0.0001) (SI Figure S9) Figure 2. Correlation between the population densities and halogenated flame retardant (HFR) concentrations for the council districts of Hong Kong.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…46,47 The relative abundances of TBB and TBPH were also quite small (<1%), probably because the commercial product Firemaster 550 containing these chemicals was only introduced in 2003. 48 A positive correlation (r 2 = 0.53; p < 0.0001) (SI Figure S9) Figure 2. Correlation between the population densities and halogenated flame retardant (HFR) concentrations for the council districts of Hong Kong.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…High atmospheric concentrations of BTBPE were observed in the U.S. (4À70 pg m À3 14 ) and in Guangzhou, China (3.8À67 pg m À3 35 ). EHTBB was first reported in house dust from the U.S., 15 and Lee et al reported qualitatively their worldwide occurrence within the GAPS Network. 28 In seawater, PBT, DPTE, and HBB were the most frequently detected compounds (78%, 56%, and 100% detection frequency, respectively) with concentrations from n.d.À0.4, n.d.À1.6, and 0.006À0.1 pg L À1 .…”
Section: ' Introductionmentioning
confidence: 99%
“…Their production and use are expected to mount in the coming future with the increasing regulations and phasing-out of the commercial PBDEs from the market. DBDPE and BTBPE are widespread in the environment and organisms (Gauthier et al, 2009;Hoh et al, 2005;Law et al, 2006;Stapleton et al, 2008a;Venier and Hites, 2008;Zhang et al, 2009). Recently, Zhang et al (2009) studied the temporal trend of DBDPE and PBDE in Dongjiang River which runs through Dongguan city, one of the largest manufacturing bases of electronic products in South China.…”
Section: Introductionmentioning
confidence: 99%